Priming with Religion and Supernatural Agency Enhances the Perception of Intentionality in Natural Phenomena - Nieuwboer, Wieteke (Journal for the cognitive science of religion, 2014)
Cognitive theories of religion suggest that belief in supernatural agents finds a basis in the human tendency to (over) detect agency in the environment. The present research investigated whether activation of religious concepts enhances the attribution of agency in natural phenomena. In two experiments we administered a religion prime (a religion questionnaire in Experiment 1; a subliminal God prime in Experiment 2) and measured the amount of intentionality and free will that participants ascribed to images of natural phenomena and agents. In both experiments participants ascribed more agency to natural phenomena if they had been presented with a religion prime. Item analyses for both experiments furthermore revealed that the effect of religious priming was most pronounced for items of natural phenomena that were perceived as beyond personal control. These findings provide empirical support for the hypothesized relation between religion and agency detection.